2020
DOI: 10.18805/ajdfr.dr-163
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sugar Reduction in the Formulation of Set-type Yogurt Using Pure Lactic Acid Bacterial Culture

Abstract: Background: Reducing the sugar content of processed products has been claimed to be one of the most efficient strategies for decreasing sugar intake. To investigate what level of sugar reduction is accepted in set-type yogurt, we conducted a hedonic test focusing on the sensory attributes and assessed the nutritional quality of the yogurt. Methods: We prepared a total of 12 set-type yogurt samples using four sugar concentrations (viz. 0, 4, 5 and 12%). The starter culture was used as a 1:1 ratio mixture of Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The lowest and highest acidity values were observed in yoghurts A (8 % sugar, 0 % milk powder and 0 % sweet apricot kernel powder) and E (0 % sugar, 8 % milk powder and 0 % sweet apricot kernel powder), respectively. According to Zahan et al ( 43 ), a total of 12 set-type yoghurt samples with four sugar mass fractions (0, 4, 5 and 12 %) were used, and the plain yoghurt had an average acidity (0.9 %) and pH (4.45). Additionally, Elkot et al ( 14 ) reported that titratable acidity and pH in yoghurt samples supplemented with detoxified apricot kernels were between 0.61 and 0.75 % and 4.55 and 4.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest and highest acidity values were observed in yoghurts A (8 % sugar, 0 % milk powder and 0 % sweet apricot kernel powder) and E (0 % sugar, 8 % milk powder and 0 % sweet apricot kernel powder), respectively. According to Zahan et al ( 43 ), a total of 12 set-type yoghurt samples with four sugar mass fractions (0, 4, 5 and 12 %) were used, and the plain yoghurt had an average acidity (0.9 %) and pH (4.45). Additionally, Elkot et al ( 14 ) reported that titratable acidity and pH in yoghurt samples supplemented with detoxified apricot kernels were between 0.61 and 0.75 % and 4.55 and 4.65, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, formulations C (5.33 % sugar, 1.33 % milk powder and 1.33 % sweet apricot kernel powder) and D (4 % sugar, 4 % milk powder and 0 % sweet apricot kernel powder) had the highest mean scores of overall acceptability, namely 6.06 and 6, respectively. According to Zahan et al ( 43 ), a higher concentration of sugar should lead to an increase in preference. However, the acceptability of sweet taste varies from consumer to consumer.…”
Section: Resultsmentioning
confidence: 99%